Women entrepreneurs in Africa : experience from selected countries (UN New YorkUS)
Presents lessons from experiences gathered by UNCTAD and UNIDO in 11 African countries. Focuses on results from country surveys of women entrepreneurs and gives illustrative examples from need assessment missions. Shows that women's full economic potential is not being tapped.
Keywords: ENTREPRENEURS